2016
DOI: 10.1111/nmo.12779
|View full text |Cite
|
Sign up to set email alerts
|

Na+/Ca2+ exchanger‐heterozygote knockout mice display increased relaxation in gastric fundus and accelerated gastric transit in vivo

Abstract: In this study, we demonstrate that NCX1 and NCX2 expressed in neurons regulate the motility in the gastric fundus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Our second strength was to evaluate and analyze the motility according to the stimulus. We are confident in the used of these methods as our laboratory has already published many papers involving the use of an isotonic transducer under EFS (Azuma et al, ; Azuma, Samezawa, Nishiyama, Nakajima, & Takeuchi, ; Fujimoto et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our second strength was to evaluate and analyze the motility according to the stimulus. We are confident in the used of these methods as our laboratory has already published many papers involving the use of an isotonic transducer under EFS (Azuma et al, ; Azuma, Samezawa, Nishiyama, Nakajima, & Takeuchi, ; Fujimoto et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In rat longitudinal gastric fundus muscle strips, a relaxant effect was produced by VIP, PACAP1–27, and secretin ( 79 ). Similarly, PACAP exerts relaxant activity on circular muscle strips from rat gastric fundus ( 80 ) and in the mouse antrum ( 81 ). In guinea pig gastric fundus, VIP, PACAP1-27 and PACAP1-38 induced concentration-dependent relaxation that was partly inhibited by the antagonists VIP10–28 and PACAP6–38 and the NO synthase inhibitor NG-nitro- l -arginine ( l -NNA).…”
Section: Effects Of Pacap In the Stomachmentioning
confidence: 99%
“…We previously demonstrated that NCX2 HET, but not NCX1 HET, displays altered motility in the distal colon (Azuma et al, 2012). In addition, we recently demonstrated that NCX1 HET and NCX2 HET display altered motility in the gastric fundus (Azuma et al, 2016a). Currently, little is known about the potential role of NCX isoforms in small intestinal motility.…”
Section: Introductionmentioning
confidence: 99%